Dark Deformations and Light Pulsations of Cosmic Medium (Global Journal of Science Frontier Research, 2017)
The suggested constructions are related closely to fluid motion and devoted mainly to get affirmative answers for the known astronomy questions originated in the first half of the last century. As observations continue to evidence, the light, or visible part of universe is not in the void, but is submerged in the invisible dark matter that complements the former up to a general cosmic medium filling all the space. Bellow, such a medium is supposed to be mobile and described with vector field of velocities and matrix fields of fluid deformations and turbulent stresses prevailed in its dark and light parts of universe, respectively. Any dark part is invisible because it’s laminar, or it does not produce any turbulent stresses. Moreover, it does not obligated to obey the classical laws of mass, momentum and energy conservation, instead of which the principle of least deformation is assumed to be valid in it. And the latter provides what is known to be a central expansion of medium including the so called Hubble constant and two stagnation points of source and sink. The light part is visible because its domain contains a turbulent kernel which medium pulsates finely and generates the field of turbulent stresses. And small disturbances of this field when coupled with that of average velocity field propagate throughout the light part in the form of electromagnetic waves. 2 As this takes place, the visible motion of the light component of cosmic medium is proposed to be relative corresponding to the bulk flow of its dark part, which leads to additional inertial forces.
Keywords: the dark (light) part of universe as a laminar (turbulent) medium; the principle of the least deformation; the turbulent nature of electromagnetic wav